Corporate governance practices and capital structure decisions: the moderating effect of gender diversity - Amarkai Lartey Chelsea (KNUST, 2024)
A thesis submitted to the department of accounting & finance, kwame nkrumah university of science and technology, kumasi in partial fulfilment of the requirements for the award degree of masters of science accounting & finance